Implementasi Extract Transform Load Pada Data Akademik Perguruan Tinggi - Nahrun Hartono; Didit Hermawan (Journal Software, Hardware and Information Technology, 2021)
Each department at university needs to analyze student data and scores. By analyzing student grades, majors can improve lecturer performance in learning; one way to explore student grades is to collect student grade data and then process the data to produce information in the form of learning performance results that can be used to make decisions to improve lecturer performance. The author will analyze a structured programming course student score data; the following collected data are related to student attendance, assignment scores, mid-semester exam scores, and final semester exam scores. After all the data needed has been organized to build the data warehouse, the following process is the ETL process (Extract, Transform, and Load), as the tool used in the ETL process is Pentaho. This data extraction process using 1 data source, namely student value data with excel file type. After carrying out the extraction process, there is a data transformation process, namely making some changes to the extracted data to make it more consistent and uniform according to the needs of the data warehouse.